2016
DOI: 10.17675/2305-6894-2016-5-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Mild steel protection in acidic media using Mucuna pruriens seed extract

Abstract: The inhibition of corrosion of mild steel in 1 molar hydrochloric acid solution (1 M HCl) by Mucuna pruriens seed extract (MPSE) was investigated by weight-loss and electrochemical techniques. A significant decrease in the corrosion rate of mild steel was observed in the presence of the investigated additive and the inhibition efficiency was found to depend on the concentration of the MPSE. The potentiodynamic polarization data indicated that this additive was of mixed type, but the anodic effect was more pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
(36 reference statements)
0
14
0
1
Order By: Relevance
“…where A is the frequency factor, E a is the apparent activation energy, R is the constant for ideal gases and T is the absolute temperature. An alternative formulation of the Arrhenius equation is (36)…”
Section: Weight-loss Measurementsmentioning
confidence: 99%
“…where A is the frequency factor, E a is the apparent activation energy, R is the constant for ideal gases and T is the absolute temperature. An alternative formulation of the Arrhenius equation is (36)…”
Section: Weight-loss Measurementsmentioning
confidence: 99%
“…[27] In this study, eight major components were identified ( Table 2). According to the literature, [28][29][30] fatty acids (3-6 in Table 2) and β-Sitosterol Table 2) are the main responsible for the reduction of the corrosion rate.…”
Section: Resultsmentioning
confidence: 99%
“…2 that inhibition efficiency of wheat starch increased with increasing immersion time, reaching the maximum efficiency on days 3 and showed gradual decrease in the subsequent days. The increase in inhibition efficiency with time may be attributed to strong stability of the glucose components adsorbed on the mild steel surface whereas the decrease in inhibition efficiency with time reflects desorption of glucose components from the mild steel surface, resulting in a reduced surface coverage [36].…”
Section: Weight Loss Measurement Resultmentioning
confidence: 99%